The Effect of Emotional Intelligence on Burnout with Job Stress As a Mediating Variable in Employees of the Bank Nagari Cabang Pulau Punjung: The Effect of Emotional Intelligence on Burnout with Job Stress As a Mediating Variable in Employees of the Bank Nagari Cabang Pulau Punjung - Rahman, Ferdi; Zona, Mega Asri (Human Resource Management Studies, 2025)
This study aims to analyze the effect of emotional intelligence on burnout with job stress as a mediating variable in employees of Bank Nagari Cabang Pulau Punjung. This research uses a quantitative approach with a causal research type. The population in this study included all 47 employees of Bank Nagari Cabang Pulau Punjung. The sampling technique used the total sampling method, and data collection was carried out through distributing closed questionnaires with a Likert scale. The data analysis technique was carried out with a Structural Equation Modeling (SEM) approach based on Partial Least Square (PLS) using SmartPLS 4 software. This study implies that job stress management is an important factor in efforts to reduce the risk of burnout in employees. In addition, although emotional intelligence plays an important role in managing emotions and work pressure, it does not necessarily reduce burnout without adequate management of job stress. Therefore, it is important for organizations to develop job stress management strategies and emotional intelligence training on an ongoing basis to maintain employee well-being.